Pengaruh Social Media Marketing Terhadap Intention To Visit Wisatawan Muslim Pada Destinasi Wisata Halal Di Indonesia - Velly Priliana (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2020)
Indonesian is a country with the largest Muslim population, with a number reaching 87.18% of the population of 232.4 million people in 2018. In 2015, Indonesia was the first warning of interactions regarding halal lifestyle, this has a good potential to increase the development of halal tourism in Indonesia. The digital age has become an important part in the development of halal tourism because it has now entered the era of the industrial revolution 4.0. In 2018, internet users in Indonesia are around 64.8% and the main reason for using the internet is to communicate. Social Media as the most chosen platform for communication.This study aims to determine the effect of social media marketing on Muslim tourist interest in halal tourist destinations. This research uses a quantitative approach with SEM analysis which is processed through Lisrel. The survey was conducted on 304 respondents. The exogenous variables used are Social Media Marketing, Sharia Compliance in Social Media Marketing, and Sharia Compliance in Destination, while the endogenous variables used are Attitude Towards Destination and Intention to Visit. The results obtained, social media marketing and sharia compliance in destination have a positive relationship on attitude, and attitude has a significant effect on intention, while sharia compliance in social media marketing has no significant effect on attitude. Based on these results, many factors that cause social media complicity with sharia rules are not significant to tourist attitudes. The way to do this is to develop social media that specifically addresses halal tourism.